ФАН ВА ТИЛНИ ИНТЕГРАЛЛАШГАН ҲОЛДА ЎҚИТИШ (CLIL) ДАРСЛАРИДАГИ МУАММОЛАР ВА УЛАРНИ ҲАЛ ҚИЛИШДА ЎҚИТУВЧИ МАҲОРАТИ - Хусанова, М. (SCIENCE and SOCIETY, 2018)
The article focuses on the basic impediments that every teacher faces while using CLIL approach in the classroom and on a teacher‘s competence to overcome potential barriers that may linger learning and teaching process.
Keywords: CLIL; ўқитувчи маҳорати; CLIL дарсларида ўргатиш ва ўқитишдаги муаммолар